2019
DOI: 10.7251/zrefis1918083a
|View full text |Cite
|
Sign up to set email alerts
|

Research of Conditions for Development of Public-Private Partnership Concept

Abstract: Public-Private Partnership (PPP) is a contractual relationship that integrates resources of the public and private sectors in the function of more efficient building public services. Over time, national governments have accepted, developed and organized Public-Private Partnerships in various ways, by respecting its historical and cultural context, the legal framework and the economic environment. The goal in this paper is to identify key factors that may have an impact on the development of public-private part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ireland and the United Kingdom are one of the most mature PPP markets. Over the last two decades, 24 projects of total capital value of over €5 billion have been implemented [4]. O'Shea and coauthors state that the Ministry of Public Expenditure and Reform in the Review of the Capital Plan 2016-2021 identified three phases in the development of PPPs in Ireland [40]: (1) the first phase of the PPP development was focused on travel infrastructure and primary education, (2) the second phase of development was concerning social housing, (3) while the third included projects regarding higher education, health, and courts.…”
Section: Review Of Previous Research In This Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Ireland and the United Kingdom are one of the most mature PPP markets. Over the last two decades, 24 projects of total capital value of over €5 billion have been implemented [4]. O'Shea and coauthors state that the Ministry of Public Expenditure and Reform in the Review of the Capital Plan 2016-2021 identified three phases in the development of PPPs in Ireland [40]: (1) the first phase of the PPP development was focused on travel infrastructure and primary education, (2) the second phase of development was concerning social housing, (3) while the third included projects regarding higher education, health, and courts.…”
Section: Review Of Previous Research In This Areamentioning
confidence: 99%
“…Grimsey and Lewis indicate that a Public-Private Partnership "fills a space between traditionally procured government projects and full privatization" [3]. Over time, national governments have accepted, developed, and organized Public-Private Partnerships in various ways, respecting their historical and cultural context, legal framework, and economic environment [4]. Advanced Public-Private Partnerships (PPP) markets have also developed Public-Private Partnerships in areas traditionally being taken care of by public sector.…”
Section: Introductionmentioning
confidence: 99%